(untitled) (Scientia Agropecuaria, 2023)
This study aimed to evaluate the effect of five cooking methods (steam, grill, oven, frying and microwave) on farm-raised rainbow trout’s sensory acceptability, physicochemical characteristics, and nutritional value. A survey was conducted with 307 consumers to create a marinade made with salt, garlic, cumin and pepper. The fillets marinated in this mixture were cooked, and photographs were taken to determine their sensory profile using the Check All That Apply (CATA) method, as well as their appearance through both visual (n = 289) and virtual (n = 100) surveys. Similarity was found between the sensory attribute maps for frying, oven and grilling in both evaluation methods. Significant differences (p < 0.05) in proximal composition were observed between the cooking techniques studied because of their technological parameters. The methods with the best visual acceptability were frying and microwave, and they caused an increase in the peroxide index. The n-6/n-3 ratio for both techniques (3.62 and 2.05) was within the requirement, being higher in frying due to the predominance of Omega 6 fatty acids incorporated by the oil used. This study demonstrated that the Peruvian consumer prefers cooking techniques characterized by ease of preparation and marked the development of color and texture attributes.